A 14-Year-Old Boy with Neurogenic Thoracic Outlet Syndrome: A Case Report - Dharma, I wayan Manacika Surya; Priyanto, Bambang; Febrianto, Rudi; Nandana, Pandu Ishak; hidayatullah, Audi; Antara, Komang Yose; Firdaus, Farizka; Sunanto; Istikharoh, Umu; Fatrahady, Lalu Shaktisila; et al. (Lombok Health And Science Journal, 2022)
Background: Thoracic outlet syndrome (TOS) is a complex condition that involves the neurovascular bundle located between the scalene triangle and the inferior border of the axilla. TOS represents a wide variety of clinical symptoms and there is no single test available for establishing the definitive diagnosis. This case report aims to report the clinical history, clinical features, imaging findings, and treatment of a patient with neurogenic TOS secondary to suspected cervical muscle compression due to cervical dextroscoliosis, accompanied by patent ductus arteriosus. Case Presentation: A-14 years-old boy reported progressive weakness in his right hand. The patient also complains of headaches and tiredness every time after exercise since 3 years ago and progressive loss of body weight. Physical examination revealed a lower motor neuron type of superior paraparesis with gradual progressive onset on the right upper limb, accompanied by weakness of the deltoid, biceps, triceps, and finger muscles. Adson’s test of the right upper limb showed positive results. MRI and CT scan of the spine showed a cervical dextroscoliosis causing a mild bilateral neural stenosis and minimal right thoracal scoliosis. A continuous murmur grade 3/6 intercostal space II-III was heard on heart auscultation. Echocardiography showed a patent ductus arteriosus. The patient was scheduled for electromyography and nerve conduction velocity test. Discussion: Neurogenic TOS is a chronic compressive brachial plexopathy where the brachial plexus is pressed anteriorly and upwardly by the cervical rib arising elongated transverse process of C7, with the symptoms characterized by pain, tingling, numbness, or motoric weakness in the upper or lower arm. Multiple tests and examinations are needed to establish a definitive diagnosis. Treatment available for neurogenic TOS included conservative treatment with physiotherapy for posture and shoulder movement correction. Conclusion: TOS is a condition that could cause a variety of symptoms. Appropriate investigations and multiple diagnostic tests are needed for establishing the diagnosis. Patient’s history, clinical presentation, and examination could help eliminates the differentials, with imaging and electrophysiological testing helps identify the etiology. Keywords: Thoracic outlet syndrome, patent ductus arteriosus, scoliosis